Potato glycoalkaloids detection based on conductometric sensor coupled to butyryl cholinesterase - Nazarenko, E.A.; Soldatkin, A.P.; Martelet, C.; Korpan, Ya.I. (Біополімери і клітина, 2004)
For the construction of a biosensor sensitive to some steroidal glycoalkaloids a conductometric planar electrode as a transducer and the horse serum butyryl cholinesterase (BuChE) as a biorecognition element have been used. It has been shown that α-solanine, α-chaconine and solanidine can be detected within the range of their concentrations from 0.2 to 100 mM depending on the type of steroidal alkaloid used. The detection limits were estimated to be 0.2 mM for chaconine and 0.5 mM for solanine/solanidine. The responses of the sensors developed were reproducible: the relative standard deviation was about 1.5 % and 5 % for intra- and inter-sensor responses, respectively. Moreover, one sensor with the immobilized enzyme can be used repeatedly (for at least 100 measurements) after a simple washing by buffer and can be stored at room temperature without substantial loss in activity of the immobilized enzyme not less than 1 month. It has been shown that all the analytes investigated inhibit reversibly and competitively the horse BuChE immobilized on the transducer surface. In assays, which combined α-solanine and α-chaconine, inhibition of BuChE was not additive. A possibility to apply the biosensor developed for the quantitative detection of the total steroidal alkaloids pool in foodstuffs and some biological samples is discussed. При створенні біосенсора, чутливого до стероїдних глікоалкалоїдів, застосовано кондуктометричний планарний електрод як перетворювач і бутирилхолінестеразу (БуХЕ) як чутливий елемент. Соланін, чаконін та соланідин визначали в діапазоні концентрацій 0,2—100 мкМ залежно від типу алкалоїду. Мінімальні концентрації, які визначаються за допомогою біосенсора, становлять 0,2 мкМ для чаконіну та 0,5 мкМ для соланіну/соланідину. Відносні стандартні внутрішньо- та міжсенсорні похибки складали 1,5 та 5 % відповідно. Крім того, той самий сенсор з іммобілізованим ферментом після відмивання в буфері можна багаторазово використовувати (щонайменше 100 вимірів) та зберігати за кімнатної температури без суттєвого зменшення активності іммобілізованого ферменту протягом місяця. Доведено, що всі досліджені речовини конкурентно та оборотно пригнічують кінську БуХЕ, іммобілізовану на поверхні перетворювача. При дослідженні спільної дії α-соланіну та α-чаконіну додаткового пригнічення БуХЕ не спостерігалося. Обговорюється можливість застосування розробленого біосенсора для кількісного визначення загальної фракції стероїдних глікоалкалоїдів у харчових продуктах та деяких біологічних зразках. Для создания биосенсора, чувствительного к стероидным гликоалкалоидам, использовали кондуктометрический планарный электрод в качестве преобразователя и бутирилхолинэстеразу (БуХЭ) как чувствительный элемент. Соланин, чаконин и соланидин определяли в диапазоне концентраций 0,2–100 мкМ в зависимости от типа алкалоида. Минимально определяемая концентрация для чаконина – 0,2 мкМ, для соланина/соланидина – 0,5 мкМ. Относительные стандартные внутри- и межсенсорные ошибки составили 1,5 и 5 % соответственно. Кроме того, один и тот же сенсор с иммобилизованным ферментом после простого отмывания буфером можно многоразово использовать (по меньшей мере, 100 измерений) и хранить при комнатной температуре без значительной потери активности иммобилизованного фермента в течение месяца. Показано, что исследуемые вещества конкурентно и обратимо ингибируют лошадиную БуХС, иммобилизованную на поверхности преобразователя. При исследовании совместного действия α-соланина и α-чаконина дополнительного ингибирования БуХЭ не наблюдалось. Обсуждается возможность применения разработанного биосенсора для количественного определения общей фракции стероидных гликоалкалоидов в пищевых продуктах и некоторых биологических образцах.